PENGARUH MOTIVASI KONSUMEN, PERSEPSI KUALITAS, SIKAP KONSUMEN DAN HARGA TERHADAP KEPUTUSAN PEMBELIAN MOBIL NISSAN GRAND LIVINA DI DEALER PUSAT PT NISSAN MOTOR INDONESIA JL. MT HARYONO KAV. 10 JAKARTA TIMUR - Ch. Endah Winarti (KELOLA, 2015)
The purpose of this reserach was to analyze Influence Consumer Motivation, Quality Perception, Consumer Attitudes and Purchase Price Decision about Purchasing Decision Nissan Grand Livina Cars at The Dealer Center of Nissan Motor Indonesia Corporation in M.T. Haryono Kav.10, East Jakarta . The method used in this research is Surveying Method using a Questionnaires. The analysis tool used is multiple linear regression. The results from this research showed that the Purchasing Decision Nissan Grand Livina Cars at The Dealer Center of Nissan Motor Indonesia Corporation in M.T. Haryono Kav.10, East Jakarta influenced by the Consumer Motivation, Perceived Quality, Consumer Attitudes, and Price. The biggest factor affecting the purchase decision is price. Keywords: Consumer Motivation, Perceived Quality, Consumer Attitudes, Price, Purchase Decision